1977
DOI: 10.1002/pssa.2210400217
|View full text |Cite
|
Sign up to set email alerts
|

Infra-red reflectivity of non-stoichiometric ferrous Oxide

Abstract: The optical properties of ferrous oxide are investigated at ordinary temperature through infrared reflectivity measurements. The experimental spectrum is well interpreted within the LO‐phonon‐plasmon interaction theory, including damping processes which cannot be neglected, mainly for the plasmon effect. The optical constants of FeO are obtained to ωTO = 333.7 cm−1, ωLO = 493.5 cm−1, ϵ∞ = 11.1, and ϵb = 24. From the model parameters of the classical dispersion theory, other macroscopic data are deduced as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Infrared reflectivity experiments on ferrous oxide with the main focus on phonon properties and conductivity contributions of free charge carriers at elevated temperatures have been performed by Bowen et al [24], Prevot et al [51] and by Henning and Mutschke [52]. Recently, Seagle et al [53] have investigated the phonon properties and conductivity contributions of Fe 0.91 O as function of hydrostatic pressure.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Infrared reflectivity experiments on ferrous oxide with the main focus on phonon properties and conductivity contributions of free charge carriers at elevated temperatures have been performed by Bowen et al [24], Prevot et al [51] and by Henning and Mutschke [52]. Recently, Seagle et al [53] have investigated the phonon properties and conductivity contributions of Fe 0.91 O as function of hydrostatic pressure.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Recently, some of the authors have reported on the temperature dependence, having identified three distinct oscillators at 5 K [38]. FeO was investigated by means of optical spectroscopy in the FIR domain first by Bowen et al [39] and Prévot et al [40]. Spectra recorded at various temperatures are also provided in [41] and recently a pressure dependent study up to 33 GPa has been performed [42].…”
Section: Mnomentioning
confidence: 99%
“…as proposed in literature [40,42]. The second term on the right hand side represents a Drude like contribution and accounts for free charge carriers with plasma frequency Ω P and damping γ P , while each addend of the sum describes one normal mode according to a Lorentz oscillator.…”
Section: Feomentioning
confidence: 99%
“…The point defects as well as their clusters are likely to affect the dielectric and optical properties of FeO. The results of various experiments [16][17][18][19][20][21][22][23][24] indicate some peculiar behavior of the measured optical quantities in wüstite and assign it to the native defects. However, a detailed explanation of the influence of such defects on the electronic and dielectric properties of FeO remains unclear.…”
Section: Introductionmentioning
confidence: 99%